Regulating Secretory Proteostasis through the Unfolded Protein Response: From Function to Therapy. Issue 10 (October 2017) - Plate, Lars; Wiseman, R. Luke
Abstract : Imbalances in secretory proteostasis induced by genetic, environmental, or aging-related insults are pathologically associated with etiologically diverse protein misfolding diseases. To protect the secretory proteome from these insults, organisms evolved stress-responsive signaling pathways that regulate the composition and activity of biologic pathways involved in secretory proteostasis maintenance. The most prominent of these is the endoplasmic reticulum (ER) unfolded protein response (UPR), which functions to regulate ER proteostasis in response to ER stress. While the signaling mechanisms involved in UPR activation are well defined, the impact of UPR activation on secretory proteostasis is only now becoming clear. Here, we highlight recent reports defining how activation of select UPR signaling pathways influences proteostasis within the ER and downstream secretory environments. Furthermore, we describe recent evidence that highlights the therapeutic potential for targeting UPR signaling pathways to correct pathologic disruption in secretory proteostasis associated with diverse types of protein misfolding diseases. Trends: Activation of the IRE1/XBP1s or ATF6 UPR signaling pathways differentially influence ER quality control decisions for destabilized, disease-associated proteins. XBP1s- or ATF6-dependent reductions in the secretion of aggregation-prone proteins indirectly protects secretory proteostasis by lowering concentrations of these proteins available for toxic aggregation. The UPR integrates with other ER-stress-responsive pathways to directly influence secretory proteostasis through the regulated secretion of extracellular chaperones. Human ATF6 mutations indicate that chronic ATF6 activation does not globally disrupt organismal physiology. Small molecules that target ATF6 activity have significant promise to ameliorate pathologic defects in secretory proteostasis associated with etiologically diverse human diseases.